African Development Foundation - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
African Development - Foundation Created in 1984, the African Development Foundation finances small development projects designed to increase food production, to improve preventive medical services and to promote small businesses. Only projects that...